Analysis and performance assessment of a novel ORC based multi-generation system for power, distilled water and heat. (April 2018) - Yari, Mortaza; Ariyanfar, Leyli; Aghdam, Ebrahim Abdi
Abstract: In this paper, the coupling of a Humidification-Dehumidification Desalination (HDD) with an Organic Rankine Cycle (ORC) as a multi-generation system is proposed in two scenarios to generate power, distilled water and heat. The system is investigated from thermodynamic and economic viewpoints, and for achieving the best results, four organic fluids are examined in the ORC. In the first scenario, the outlet water of the ORC and HDD condensers are mixed and the flow enters to the HDD, as feed water. The heat of distilled water is absorbed by a water flow in a heat exchanger and mixed with the brine of HDD to heat production. In the second scenario, just the outlet water of the ORC condenser enters to the HDD, as feed water. The heat of distilled water is absorbed by a water flow in a heat exchanger and mixed with the brine of HDD and the outlet flow of the HDD condenser. The proposed multi-generation system works without external energy (heat). Results show that within four working fluids n-Octane has the best performance and scenario (II) produce more distilled water with higher recovery rate and lower cost. Also, scenario (II) produce more amount of heating flow, although with lower temperature and higher cost. Both of proposed scenarios have optimized in order to minimizing cost of distilled water; and scenario (I), based on its structure, has optimized to maximizing distilled water production and its recovery rate. Also, a multi-objective optimization is performed for both scenarios. Highlights: ORC is used as a novel multigeneration system for power, distillated water and heat. HDD is coupled with ORC via its condenser, in two scenarios. Scenarios (II) produces more desalinated water with lower cost than scenario (I). From technical and economic aspects, scenario (II) is better than the scenario (I). The multigeneration systems with n-octane have the best performance.